The McGovern-Dole food for education and Child nutrition program (MGD): A comparative analysis of reading comprehension gains in Central America. (March 2021) - Crea, Thomas M.; Neville, Sarah E.; Diaz-Valdes, Antonia; Evans, Kerri; Urizar, Brenda; Drummer, Emily; Acevedo, Jose; Canelas, Olga; Medina, Marlon; Mallman, Jennifer
Highlights: School feeding programs have been implemented globally for years. Little research examines how these programs are linked with reading comprehension. This study examines reading comprehension and MGD programs in Central America. Reading comprehension increased especially for children in lower grades. Planning evaluation before implementation will lead to stronger evidence. Abstract: The McGovern-Dole Food for Education and Child Nutrition Program (MGD), funded by the US Department of Agriculture (USDA), is one of the most prominent school feeding programs implemented globally. MGD's primary objective is to increase childhood literacy. Yet, despite MGD's being in operation since 2002 - and school feeding programs' being implemented in Central America for decades - few empirical studies have examined the extent to which school feeding programs are linked to increased literacy, and specifically reading comprehension. This study examines increases in reading comprehension associated with implementation of MGD over a three-year period in rural departments of Guatemala and Honduras. Specific attention is paid to differences in program design and implementation between the two countries. Results show that reading comprehension significantly increased over time in both countries. Children in lower grades showed more pronounced gains, suggesting that early intervention is important in terms of school feeding and curriculum supports. Effect sizes were greater in Guatemala but with lower scores than Honduras, though measurement differences make side-by-side interpretation difficult. These results are discussed in light of evaluation constraints that point the way towards improved research designs in the future – and to the importance of rigorous evaluation in helping secure the political will to sustain and scale up programs.